Effect of probiotic supplementation among overweight population in University Tenaga Nasional (UNITEN) / Afiq Md Yunus - Md Yunus, Afiq (Faculty of Sport Science and Recreation, 2017)
The purpose of this study was to determine the effectiveness of probiotic supplementation among overweight population in Universiti Tenaga Nasional (UNITEN). A total of sisty six sedentary people (N=66) were selected via stratified random sampling participated in this study. The subje9t's average age is 18-23 years old. Results showed that there was a significance difference (p<O.05) for fat percentage and body mass index (BMI) on overweight population after six weeks consume probiotic supplementation. For the systolic blood pressure and diastolic blood pressure the result showed that there is no significance difference on overweight population after six weeks consume probiotic supplementation. As conclusion, the findings in this study shown that the effectiveness of probiotic supplementation among overweight population for fat percentage and body mass index (BMI).